Possibilidades de exercício de cidadania em um programa de ensino de inglês para alunos da rede pública :um estudo de caso - Martins, Marjory da Motta (2015)
This paper aimed to study and to comprehend possibilities of exercising citizenship in an English program for youngsters from the public schools, called Access Program. The qualitative research approach supported the singularity of this study in order to choose the investigative procedure of a naturalistic case study (Lüdke e André, 1986). Data collection was conducted by semi-structured interviews and teaching plans reading, using documentary analysis principles. Data were analysed by Discursive Textual Analysis according to Moraes and Galiazzi (2011). The theoreticals that supported the discussion involving Education and Citizenship were Antonio Gramsci, Darcy Ribeiro and Paulo Freire, who contributed to build the arguments for this study. The authors Sérgio Buarque de Holanda, Mário Sérgio Cortella, Pedro Goergen and Cleoni Fernandes were also utilized for the discussion involving Education and Citizenship. To take into consideration the peculiarities related to English Teaching, three authors were utilized: Douglas H. Brown , Jack C. Richards and Willy A. Renandya. The study showed that the Access Program made the exercise of citizenship possible in many situations during the course, allowing students to have opportunities of critical thinking and intellectual autonomy, through motivating and liberating activities. It was also found an intersection between citizenship conception, the way it is treated theoretically, and Foreign Language Teaching, in this case English Teaching, in the sense that it is necessary to respect the right that others have to have rights and respect the other one whose language is being learned, what demands an ethical and solidary posture of recognition of alterity – an attitude of generosity.